2012
DOI: 10.1186/1479-5876-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a multianalyte test as an aid for the diagnosis of ovarian cancer in symptomatic women

Abstract: BackgroundConcomitant with the development of in vitro diagnostic multivariate index assays (IVDMIAs) to improve the diagnostic efficiency of ovarian cancer detection is the need to identify appropriate biostatistical approaches to assess improvements in risk predication. In this study, we assessed the utility of three different approaches for comparing diagnostic efficiency of an ovarian cancer multivariate assay in a retrospective case - control phase 2 biomarker trial. The control cohort included both disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…The result of meta-analysis of 20 studies with 3682 patients and 2424 healthy individuals were consistent with the findings of Zhang et al ,14 Cho et al ,15 Wang et al ,16 Autelitano et al ,20 Cocco et al ,21 Wang et al 30 and Edgell et al ,31 showing the strong relationship between SAA levels and cancers. Furthermore, these findings indicated that high SAA levels were certainly correlated with the occurrence and development of cancers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The result of meta-analysis of 20 studies with 3682 patients and 2424 healthy individuals were consistent with the findings of Zhang et al ,14 Cho et al ,15 Wang et al ,16 Autelitano et al ,20 Cocco et al ,21 Wang et al 30 and Edgell et al ,31 showing the strong relationship between SAA levels and cancers. Furthermore, these findings indicated that high SAA levels were certainly correlated with the occurrence and development of cancers.…”
Section: Discussionsupporting
confidence: 87%
“…There were 14 articles with high methodological quality, including the studies of Zhang et al ,14 Cho et al ,15 Wang et al ,16 Toriola et al ,19 Autelitano et al ,20 Cocco et al ,21 Wood et al ,22 Kanoh et al ,23 Benson et al ,24 Kimura et al ,25 Khan et al ,26 Chan et al ,27 Dai et al 28 and Liu et al 29. The studies of Cocco et al ,13 Wang et al ,30 Edgell et al ,31 Kim et al ,32 Sung et al 33 and Biran et al 34 had low methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Each of biomarkers displayed significantly elevated serum concentrations in ovarian cancer patient compared with either benign [9]. …”
Section: Sample Collectionmentioning
confidence: 96%
“…CA125 is most widely used serum biomarker for diagnose for ovarian cancer [8]. CA125 was elevated in only 50% of stage I ovarian cancer cases and in 69% of ovarian tumours while being far more prominently expressed in patients with late stage serous tumours [9]. Thus, CA125 has low sensitivity in early-stage disease and additional ultrasonography or combinations of other markers are required [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation